2020
DOI: 10.1167/iovs.61.2.35
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Retinal Vessel and Retinal Layer Thickness After Vitrectomy in Retinal Detachment via Swept-Source OCT Angiography

Abstract: Citation: Hong EH, Cho H, Kim DR, Kang MH, Shin YU, Seong M. Changes in retinal vessel and retinal layer thickness after vitrectomy in retinal detachment via swept-source OCT angiography. Invest Ophthalmol Vis Sci. 2020;61(2):35. https://doi.org/10.1167/iovs.61.2.35 PURPOSE.To compare postvitrectomy retinal and choroidal vessel density (VD) and retinal layer thickness between eyes with macula-off and macula-on rhegmatogenous retinal detachment (RRD) using swept-source optical coherence tomography (SS-OCT) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 31 publications
5
55
2
1
Order By: Relevance
“…Table 3 describes a comparison study between this study and some recent literature on a similarly treated group of RRD. [29][30][31] This study has some limitations in its design related due to the small sample size and shorter follow-up compared to some previous studies. Use of silicone oil-based tamponade in all cases may cause some imaging artifacts and can affect post-operative vision.…”
Section: Discussionmentioning
confidence: 93%
“…Table 3 describes a comparison study between this study and some recent literature on a similarly treated group of RRD. [29][30][31] This study has some limitations in its design related due to the small sample size and shorter follow-up compared to some previous studies. Use of silicone oil-based tamponade in all cases may cause some imaging artifacts and can affect post-operative vision.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, the choriocapillary layer (CCP) was investigated in patients undergoing surgery for RRD repair [ 26 , 27 ]. In macula-OFF patients with an outer retinal defect, CCP vascular density was significantly correlated to VA, hypothesizing that choroidal vascularization can affect the IS/OS segment trophism.…”
Section: Discussionmentioning
confidence: 99%
“…Following vitreo-retinal (VR) surgery in RRD, using SSOCTA, Hong et al (2020) found that the vascular densities in superficial and deep capillary plexus in the detached eyes did not differ significantly from those in the fellow eyes. Their eyes had a short onset duration (of 6-8 days) for RRD before undergoing surgery.…”
Section: Discussionmentioning
confidence: 98%
“…The central retinal artery forms the superficial capillary plexus (SCP); central retinal artery and choriocapillaris supplying outer plexiform layer form deep capillary plexus (DCP); while the choriocapillaris supply the retinal pigment epithelium, photoreceptor layer, external limiting membrane and outer nuclear layer. The choroidal circulation supplies foveal avascular zone (FAZ) (Hong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%